The Assessment of the Management of Technological Changes in the Croatian State Administration Bodies - Dukić, Gordana; Dukić, Darko; Bertović, Neven (Oeconomica Jadertina, 2017)
The aim of this paper was to explore the management of technological changes in Croatian state administration bodies. The study was based on government employees’ attitudes. Due to the close connection between technological changes and e-government, their satisfaction with e-services is also examined in the study. According to the results, the respondents were only slightly satisfied with the technological changes in their organizations and e-services provided by the government. The attitudes of employees with regard to age, gender, level of education and position within the institution were quite similar. The analysis further revealed that government employees are mostly dissatisfied with the management of technological changes. In addition, a k-means cluster analysis was used to classify respondents into two groups according to their satisfaction levels. However, there was no significant relationship between employees’ characteristics and their belonging to a specific cluster. Since the management of technological changes in public administration has been insufficiently explored, this study provides valuable information for scholars, policy makers and practitioners.